Homeostasis of mucosal glial cells in human gut is independent of microbiota - Inlender, Timna (Sci Rep, 2021)
In mammals, neural crest cells populate the gut and form the enteric nervous system (ENS) early in embryogenesis. Although the basic ENS structure is highly conserved across species, we show important differences between mice and humans relating to the prenatal and postnatal development of mucosal enteric glial cells (mEGC), which are essential ENS components. We confirm previous work showing that in the mouse mEGCs are absent at birth, and that their appearance and homeostasis depends on postnatal colonization by microbiota. In humans, by contrast, a network of glial cells is already present in the fetal gut. Moreover, in xenografts of human fetal gut maintained for months in immuno-compromised mice, mEGCs persist following treatment with antibiotics that lead to the disappearance of mEGCs from the gut of the murine host. Single cell RNAseq indicates that human and mouse mEGCs differ not only in their developmental dynamics, but also in their patterns of gene expression.